PENGELOLAAN RISIKO TABUNGAN EMAS DI PEGADAIAN SYARIAH - Ana Zuliatin Nadhiroh; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
Islamic pawnshop in Blauran is the official goverment institutions that do funding in the form of lending with the basis of legal pawn based on Islamic Shariah. Islamic pawnshop has many products and among is gold saving.This research uses descriptive qualitative approach. This research uses case study method.Technique of data collection is done by participant observation, semiterstruktur interview, and documentation. The result of this research can be concluded that blueprint pawnshop implements risk management of gold saving product with three stages, that is, risk identification by identifying any risks attached to gold saving by tracing the cause of the risk, evaluation and measurement of risk by making frequency and significance matrix and risk management by doing risk mitigation such as there are institutions of audit and there are promote from Islamic pawnshop.    REFERENCESAlqur’an At-Thayyib (Al-qur’an Transliterasi Perkata dan Terjemahan Perkata). Bekasi: Cipta Bagus Segara Bungin, Burhan. 2001. Metodologi Penelitian Kualitatif. Jakarta: PT. Raja Gapindo PersadaHadi, A. Chairul. Januari 2012. Menimbang Gadai Emas Sebagai Instrumen Investasi Syariah,, (Online). Jurnal vol IV no, 2), (www.googleschoolar.com didownload tanggal 20 Februari 2017)Hanafi, Mamduh M. 2014. Manajemen Risiko, Yogyakarta: UPP STIM YKPNHuda, Nurul dan Mohamad Heykal 2010. Lembaga Keuangan Islam, Jakarta: Kencan Prenada Media Group Kasidi. 2010. Manajemen Risiko, Bogor: Ghalia IndonesiaKhan, Tariqullah dan Habib Ahmed.  2008. Manajemen Risiko Lembaga Keuangan Syariah, Jakarta: Bumi AksaraPeraturan Otoritas Jasa Keuangan nomor 65/POJK.03/2016. 2016. PENERA[AN MANAJEMEN RISIKO BAGI BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH. (online) (di download 5 Juli 2017)PT. Pegadaian Syariah.2016. Tabungan Emas.  (Online), (www.pegadaiansyariah.co.id diakses pada tanggal 18 Februari 2017)Satori, DJm’an dan Aan Komariah. 2009. Metodologi Penelitian Kualitatif, Bandung: AlfabetaSoedarso, Heri. 2008. Bank dan Lembaga Keuangan Syariah, Yogyakarta: EkonisiaSugiyono. 2014. Metode Penelitian Kuantitatif, Kualitatif, dan R&D, Bandung: CV. AlfabetaSuryomurti, Wiku. 2011. Super Cerdas Investasi Syariah, Jakarta:QultumMediaSyafe’i, Rachmad. 2001. Fiqh Muamalah, Bandung: CV. Pustaka SetiaYin,R. K. 2009. Studi Kasus; Desain dan Metode, Jakarta; Raja Grafindo Persada Yuliana, Indah. 2010. Investasi Produk Keuangan Syariah. Malang: UIN MALIKI PRESS (ANGGOTA IKAPI MALANG)